Molybdenum Application on the Growth and Nutrient Element Contents of Head Lettuce (Lactuca sativa L.) in Acid Soils - Adiloglu, Sevinc; Adiloglu, Aydin; Sumer, Ali; Satana, Aziz (Asian Journal of Chemistry, 2010)
This work was carried out in order to determine the effects of increasing molybdenum application on some nutrient element contents of head lettuce plant in acid soil under greenhouse conditions. For this purpose, an experiment was done under greenhouse conditions with three replications and head lettuce was grown. Three different doses of Mo (0; 0.25 and 0.50 mg kg-1) (in (NH4)6Mo7O2·4H2O form) were applied to plants. Nitrogen fertilizer was applied to experiment area 100 mg kg-1 as NH4NO3 whereas phosphorus fertilizer was applied to experiment area 50 mg kg-1 as KH2PO4. According to the results, N, P and K contents of head lettuce increased with increasing of Mo applications. Fe, Zn and Mn contents of plant decreased with increasing of Mo applications, while Cu content of plant was not affected. All these effects were statistically significant at the confidence level of 1 %.